Efek pH Terhadap Pelepasan Fosfat Oleh Lumpur Aktif Dalam Kondisi Anaerob - Jubhar Christian Mangimbulude (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2003)
Phosphate removal  in domestic wastewater or  industrial wastewater is a key factor of prevent eutrophication. Mechanisms of  biological  phosphate removal occurs  under both  of anaerobic and aerobic conditions.  Phosphate up take under aerobic condition  is much determined by phosphate released under anaerobic condition. The objective of this research was  to  understand the effect of  various of  external  pH  on phosphate released  by  activated sludge  under anaerobic conditions. For that purpose, the  experiments were  conducted  in  batch system  under anaerobic condition  at  pH of  6.0, 7.0, 8.0 and 9.0   separetely. PO4, Acetate  and MLVSS  were  measured  and  used  as  parameters to  analyze  process.  The results shown  that the highest of  phosphate released  and acetate consumed occurred at pH 9.0 and the lowest it was occurred at pH 6.0. The value of   phosphate/acetate ratio was calculated to be in variation  of 0.161  to 0.256  p-mol/C-mol  in  pH  range  of 6.0  to 9.0